fill in the table using the function rule y=-6x+3 fill in y

x -1 y

x 0 y

x 1 y

x 5 y

y = - 6x + 3

Put x = -1 then

y = - 6(-1) + 3 = 6 + 3 = 9

Put x = 0 then

y = - 6(0) + 3 = 0 + 3 = 3

Put x = 1 then

y = - 6(1) + 3 = - 6 + 3 = - 3

Put x = 5 then

y = - 6(5) + 3 = - 30 + 3 = - 27

Hence the table is

x = -1 then y = 9

x = 0 then y = 3

x = 1 then y = - 3

x = 5 then y = - 27

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up